Justification of a dual ventilation system for the complete burial of high-level radioactive waste in spent open mines - Kaiym, Talgat; Tuleshov, Amandyk; Seidakhmet, Askar; Kaimov, Suleimen; Kaimov, Aidarkhan; Kaimov, Abylay; Zamanbek, Azil; Abussagatov, Yelaman; Alibek, Aliman; Issabayev, Kaiyrtay (Eastern-European Journal of Enterprise Technologies, 2025)
The complete burial of high-level radioactive waste (HLW) in spent open mines presents a promising solution to long-term waste isolation. This study presents the justification and design of an innovative dual ventilation system aimed at regulating heat and removing gas-dust mixtures from such repositories. The ventilation system is designed to control dust-gas emissions and thermal loads through a two-chimney configuration, enabling efficient gas extraction and convective cooling. A system of main and additional chimneys is proposed: the main chimney channels the rising hot gas-dust mixture, while the additional chimney processes it through a staged treatment system before final disposal. Mathematical modeling, including Fourier’s Law, Darcy’s Law, and Fick’s Law, supports the thermal, hydraulic, and gas dynamics simulations. The study demonstrates that with adequate ventilation flow and composite-layer insulation, internal repository temperatures can be reduced from 300°C to below 100°C within 30 years, significantly lowering the risk of container degradation and gas-induced particle mobilization. The integrated system improves the safety, observability, and long-term reliability of HLW burial in open spent mines, offering a scalable and internationally compliant solution. Through a combination of temperature distribution modeling, structural analysis, and airflow simulations, the system's viability is demonstrated. The results show that the proposed ventilation configuration provides effective thermal regulation, structural resilience under stress, and compatibility with repurposed mining infrastructure. The study contributes a scalable, energy-efficient solution to HLW (High-level radioactive waste) repository management, paving the way for safer and more sustainable nuclear waste isolation